2021
DOI: 10.1108/lht-05-2021-0161
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing response quantity on academic social Q&A sites: a multidiscipline comparison of linguistic characteristics of questions

Abstract: PurposeAs academic social Q&A networking websites become more popular, scholars are increasingly using them to meet their information needs by asking academic questions. However, compared with other types of social media, scholars are less active on these sites, resulting in a lower response quantity for some questions. This paper explores the factors that help explain how to ask questions that generate more responses and examines the impact of different disciplines on response quantity.Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…sociology, folklore, politics and anthropology. Li et al (2023) analyzed the linguistic characteristics of the academic social Q&A platforms in ResearchGate. They show that such platforms can assist scholars in having improved scholarly communications.…”
Section: Bibliometric and Related Studies On Social Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…sociology, folklore, politics and anthropology. Li et al (2023) analyzed the linguistic characteristics of the academic social Q&A platforms in ResearchGate. They show that such platforms can assist scholars in having improved scholarly communications.…”
Section: Bibliometric and Related Studies On Social Networkmentioning
confidence: 99%
“…Wide-spread and high-quality online information services have provided alternative sources during the lockdown (Ding et al , 2021; Hsieh et al , 2023; Lo and Chiu, 2015; Lo et al , 2015, 2017; Suen et al , 2020; Dong et al , 2021; Sun et al , 2022; Wang et al , 2016; Wong and Chiu, 2023; Fan and Liu, 2022; Zuo et al , 2023; Cheng et al , 2022; Cheng, 2022; Wang et al , 2022; Wong et al , 2023) and people have further changed their information and learning habits to digital, particularly for the newer generation (Chan et al , 2022; Chan et al , 2020; Dai and Chiu, 2023; Guo et al , 2022; Shahzad and Khan, 2022; Soroya and Faiola, 2023; Sung and Chiu, 2022; Yi and Chiu, 2023; Wai et al , 2018; Wong and Chiu, 2023; Yu et al , 2022; Zhang et al , 2021). Moreover, the pandemic has accelerated service transformation (Chan et al , 2022; Cheng et al , 2022; Chin and Chiu, 2023; Khan and Ayesha, 2022; Khan et al , 2022; Li et al , 2023; Li et al , 2023; Lin et al , 2022; Lo et al ., 2020; Noh, 2022; Nwagwu and Matobako, 2022; Tseng and Chiu, 2022; Tse et al , 2022; Yao et al , 2023; Wong and Chiu, 2023; Wu et al , 2022b, 2023; Xue et al , 2023), especially supported by ubiquitous mobile Internet services, social media, apps and devices (Dukic et al , 2015; Ezeamuzie et al , 2022; Fan et al , 2020; Fung et al , 2016; Gong et al , 2017; Hui et al , 2023; Lau et al , 2017, 2020; Law et al , 2019; Ni et al , 2022; Yip et al , 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Readers may also be interested in recent research on design-maker communities of practice (Zhang and Hu, 2022), MOOCs continuance intention and dropout (Cheng, 2022; Wang et al , 2023b), social media information creditability and sharing issues (Khan et al , 2022; Li et al , 2023a; Ye and Ho, 2022; Yuan and Bi, 2023; Zhang et al , 2022, 2023b) and the use of social media for promotion (Liao et al , 2022; Lu et al , 2023; Wójcik, 2022a; Wu and Yang, 2022).…”
Section: Social Media and Mooc Communitiesmentioning
confidence: 99%
“…By analyzing COVID-19 tweets, one study found that topics with negative emotional polarity attracted more replies and favorites than positive tweets [36]. In academic social networking sites, questions containing linguistic features such as sadness, positive emotions, and second-person pronouns have a positive effect on response volume [37]. And in online cancer support groups, messages with highly positive emotions were less likely to receive responses [38].…”
Section: Hypothesismentioning
confidence: 99%